Public Policy for National Economic Recovery through the Coordinating Ministry for the Economy of the Republic of Indonesia - Yulivan, Ivan; Mahroza, Jonni; Widjayanto, Joni (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
In the past two years, the resilience of the national economy has been tested by shocks from the unprecedented global crisis of the COVID-19 pandemic that began to spread in Indonesia in early 2020. By implementing various policies, the government reacted quickly to revive the economy. On the contrary, the Coordinating Ministry for Economic Affairs of the Republic of Indonesia realizes that global uncertainty and challenges are the factors in government decision-making regarding the formulation of an effective and efficient national economic recovery strategy. This national economic recovery also involves the defense sector in accelerating and implementing policies. Defense economy is closely related to the use of the defense budget during peacetime. During the COVID-19 pandemic, there was a lot of refocusing, one of which was the reallocation of the defense budget to support social safety nets in the form of direct cash assistance. This research aims to find out how far the Indonesian government has gone through the national economic recovery policy after the COVID-19 pandemic in various aspects. Descriptive qualitative research methods are used. In this study, national economic recovery contains decreasing public mobility in the context of controlling COVID-19, fiscal policy as a shock absorber, price stabilization, improving the quality of human resources through the Pre-Employment Card program, encouraging MSME development through the expansion of the MSME sector, and continuing structural reforms including components that must be met regarding government policies for economic recovery and price stability, according to the study findings.